Isolation of viruses, including mollivirus, with the potential to infect Acanthamoeba from a Japanese warm temperate zone. - Daichi Morimoto; Naohisa Tateishi; Michiko Takahashi; Keizo Nagasaki (PLoS ONE, 2024)
Acanthamoeba castellanii is infected with diverse nucleocytoplasmic large DNA viruses. Here, we report the co-isolation of 12 viral strains from marine sediments in Uranouchi Inlet, Kochi, Japan. Based on the morphological features revealed by electron microscopy, these isolates were classified into four viral groups including Megamimiviridae, Molliviridae, Pandoraviridae, and Pithoviridae. Genomic analyses indicated that these isolates showed high similarities to the known viral genomes with which they are taxonomically clustered, and their phylogenetic relationships were also supported by core gene similarities. It is noteworthy that Molliviridae was isolated from the marine sediments in the Japanese warm temperate zone because other strains have only been found in the subarctic region. Furthermore, this strain has 19 and 4 strain-specific genes found in Mollivirus sibericum and Mollivirus kamchatka, respectively. This study extends our knowledge about the habitat and genomic diversity of Molliviridae.